Assessment of the pregnancy outcome in women with first trimester bleeding - V. Sravani; Saira Zia; Shaiesta Amreen; Parveen Yousuff (Al Ameen Medical College, 2024)
Introduction: First trimester bleeding is troublesome problem in pregnant women. It occurs due to various causes, some not related to pregnancy. It leads to various maternal & fetal adverse outcomes as well. Aim: To study pregnancy outcome in women with first trimester bleeding. Materials and Methods: This prospective observational study was done among 150 women with first trimester bleeding in Department of obstetrics & Gynecology, Shifaa hospital, Bangalore. Various adverse outcomes in pregnant women & neonates were observed as variables and their incidences were calculated. Results: Among 150 pregnant women, maximum adverse outcomes were seen in age group 23-26yrs, multigravidas and those with previous term pregnancies. Antepartum complications in decreasing order of frequency were PROM, Pre- Eclampsia, Abruption, Low-Lying placenta, Eclampsia. Majority of pregnant women had normal vaginal deliveries followed by cesarean and instrumental delivery. 20.7% of neonates had low birth weight who needed close monitoring in NICU. Conclusion: First trimester bleeding is considered as one of the indicator for determining fetal & maternal outcome. Knowledge regarding this aspect will help obstetricians to anticipate complications and manage them effectively.